2017
DOI: 10.1016/j.joca.2017.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative validation of quantitative T2 mapping in patients with articular cartilage lesions of the knee

Abstract: T2 mapping might provide a diagnostic tool for the detection of early knee-joint cartilage damage and for the non-invasive differentiation between ICRS grades by MRI in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 38 publications
5
29
1
1
Order By: Relevance
“…The increase in T2 mapping values in areas of damaged cartilage is in accordance with the findings of Lee et al, who reported that T2 mapping values were higher in patients with radiographically diagnosed primary glenoid OA than in those without OA 14 . Furthermore, our findings are in line with those of T2 mapping studies of OA in other joints that reported increased T2 mapping values in damaged cartilage 17 , 27 , 28 . In our study population, the highest overall T2 mapping value in normal cartilage in healthy patients (27.3 ms) and in normal-appearing cartilage in the patients with proven cartilage damage (26.0 ms) were lower than the lowest overall T2 value in the patients with cartilage damage (40.8 ms), indicating complete separation of the data in these study groups.…”
Section: Discussionsupporting
confidence: 92%
“…The increase in T2 mapping values in areas of damaged cartilage is in accordance with the findings of Lee et al, who reported that T2 mapping values were higher in patients with radiographically diagnosed primary glenoid OA than in those without OA 14 . Furthermore, our findings are in line with those of T2 mapping studies of OA in other joints that reported increased T2 mapping values in damaged cartilage 17 , 27 , 28 . In our study population, the highest overall T2 mapping value in normal cartilage in healthy patients (27.3 ms) and in normal-appearing cartilage in the patients with proven cartilage damage (26.0 ms) were lower than the lowest overall T2 value in the patients with cartilage damage (40.8 ms), indicating complete separation of the data in these study groups.…”
Section: Discussionsupporting
confidence: 92%
“…This demonstrated the superior sensitivity of T2 mapping compared to morphological MRI in the detection of mild to moderate cartilage lesions ( Table 2). Soellner et al confirmed that quantitative MRI is more sensitive to detecting early cartilage degeneration [42].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, quantitative MRI was used to monitor the effect of radiofrequency chondroplasty on grade II patellar cartilage defects. Quantitative MRI with T2 mapping was utilized because it has been shown to be an accurate and reliable method to monitor the condition of early (grade I/II) articular cartilage defects in order to avoid second-look arthroscopy [40,42]. Furthermore, Baum et al showed that T2 relaxation times are a suitable, non-invasive tool to assess early cartilage degeneration in the knee joint [23].…”
Section: Discussionmentioning
confidence: 99%
“…T2 relaxation time of cartilage is associated with collagen and tissue hydration 6,7 while T1r is sensitive to alterations in proteoglycan content 8 . Soellner et al 9 performed a validation of T2 relaxation time mapping of knee cartilage with intraoperative scoring in six compartments: patella, trochlea, central medial and central lateral femoral condyle, medial and lateral tibia plateau. They reported an increase of T2 with increasing grade of cartilage damage and established a T2 threshold value of 47.6 ms to differentiate between normal and degraded cartilage (Fig.…”
Section: Cross-sectional Studiesmentioning
confidence: 99%